Psychosocial Work Environment and Certified Sick Leave among Nurses during Organizational Changes and Downsizing - Bourbonnais, Renée; Brisson, Chantal; Vézina, Michel; Masse, Benoît; Blanchette, Caty (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2005)
The study aimed to determine whether the incidence and duration of certified sick leave (CSL) among nurses had increased during major restructuring of the health care system in the province of Québec, and to determine whether nurses exposed to adverse psychosocial factors at work showed an increased incidence of CSL. It involved nurses working in 13 health facilities. Sickness absence data were retrieved from administrative files (n = 1454). Incidence of CSL for all diagnoses and for mental health problems was examined. Telephone interviews were conducted to measure psychosocial factors at work with validated instruments. There was an increase in CSL among nurses during the restructuring, particularly for mental health problems. Modifiable adverse psychosocial work factors were identified and provide basis for interventions. Since human resources are the mainstay and primary resource of the health network, it is essential that people be able to perform their work under optimal conditions.